Postnatal depression in British mothers of African and Caribbean origin: a randomised controlled trial of learning through play plus culturally adapted cognitive behaviour therapy compared with psychoeducation - Jidong, Dung Ezekiel; Ike, Tarela Juliet; Murshed, Maisha; Francis, Christopher; Mwankon, Shadrack Bitrus; Jidong, John Ezekiel; Pwajok, Juliet Yop; Nyam, Pam Patrick; Husain, Nusrat (Frontiers in Psychiatry, 2024)
Background: One in every three women worldwide experiences postnatal depression after childbirth, with long-term negative consequences on their children. The mainstream mental healthcare provision for British mothers of African/Caribbean origin is mostly unsuccessful due to a lack of culturally appropriate care. Methods: The study adopts a mixed-methods randomised controlled trial (RCT) design. A 12-session (60 minutes each) of online Learning Through Play plus Culturally adapted Cognitive Behaviour Therapy (LTP+CaCBT) intervention was employed for treating postnatal depression in comparison with psychoeducation (PE). Participants aged 19-53 were screened for depression using the Patient Health Questionnaire (PHQ-9). N=130 participants who scored >5 on PHQ-9 were randomised into LTP+CaCBT (n=65) or PE (n=65) groups. N=12 focus groups (LTP+CaCBT, n=6; PE, n=6) and n=15 individual interviews (LTP+CaCBT, n=8; PE, n=7) were conducted, transcribed verbatim and analysed.Results: Satisfaction with intervention (LTP+CaCBT, 72.9%; PE, 65.2%); retention rates (LTP+CaCBT, 91%; PE, 71%); reduction in postnatal depression was higher in LTP+CaCBT on PHQ-9 Md=1.00 with z= -4.046; compared to PE, Md=1.00 with z= -1.504. Both groups showed reduced levels of anxiety on GAD-7 with no significant difference. Emerging themes from the qualitative findings showed increased positive moods, reduced worries about parenting difficulties and the facilitative role of remote intervention. Conclusions: LTP+CaCBT intervention is culturally appropriate and acceptable and reduces postnatal depression in British mothers of African/Caribbean origin. A fully powered RCT is recommended to evaluate the clinical and cost-effectiveness of LTP+CaCBT, including the child's outcomes compared with routine treatment as usual. Trial registration. www.ClinicalTrials.gov (no. NCT04820920).